The Power of Self-Efficacy on Narrative Writing: Evidence from an English Education Program - Fitri Nurdianingsih; Ima Isnaini Taufiqur Rohmah; Gika Septia Ramadani (Universitas Pendidikan Ganesha, 2026)
Writing skills are an essential competency in English language education, yet many students still experience difficulties in producing effective narrative texts due to linguistic limitations and low self-confidence. This problem results in the suboptimal development of coherent and creative narratives. This study aims to analyze and examine the relationship between students' self-efficacy and narrative essay writing skills. This study used a quantitative approach with a correlational design, involving undergraduate students as research subjects. Data were collected through a writing self-efficacy questionnaire and a narrative writing assignment as the main instrument. Data analysis was conducted descriptively and inferentially using technical correlation and regression to identify the strength of the relationship and the predictive contribution of self-efficacy to writing skills. The results showed that students' self-efficacy tended to be in the moderate to high category, with strengths in the aspect of developing ideas and weaknesses in the aspect of being fixated on grammar. Narrative writing skills were in the good category, although obstacles still occurred in language accuracy. The analysis showed a strong positive relationship between self-efficacy and narrative writing skills, and self-efficacy acted as a significant predictor. These findings imply the importance of learning strategies that integrate confidence building with skill development through constructive feedback writing, ongoing guidance, and structured learning experiences.